Development of pineapple-kalamansi juice drink - Donato, Maria Bridget B.; Francisco, Ma. Leonora dL. (1998)
People have started realizing the bad effects of carbonated softdrinks (CSD). The market now offers a lot of sources as possible alternative to CSD. Among these are the fruit juices. In line with this, it is but appropriate to use indigenous raw materials to produce fruit juices like pineapple-kalamansi juice drink. The optimum ratio of the pineapple and kalamansi extract was determined. This formulation was then added to different amounts of water to determine optimum water to juice blend ratio. Acceptability of the product was based on the results of the sensory evaluation. The chosen product was then heated to different temperatures - 60oC, 70oC, and 80oC. Microbiological examination was done to determine acceptability of the product together with the result of the sensory evaluation. The product heated at the optimum temperature was then compared to the fresh extracted juice drink and their physico-chemical properties were tabulated. Results showed that the 70% pineapple-30% kalamansi was the optimum ratio of the blend. The 2:1 water to juice blend produced the best result as obtained from the sensory evaluation. The optimum temperature of heat treatment was 80oC. Comparison of the processed and fresh juice drink showed no significant differences in terms of physico-chemical and sensory properties as shown in the results of the T-test for difference at 5% level of significance.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Fruit juices; Beverages